2013
DOI: 10.2485/jhtb.22.171
|View full text |Cite
|
Sign up to set email alerts
|

A Site-Specific Comparison of the Trabecular Structure in Senescence-Accelerated Mice^|^mdash;Evaluation of Time-Course Changes in Bone Architecture using in Vivo Micro-CT^|^mdash;

Abstract: Recent research on osteoporosis has led to a number of advances in our understanding of its pathophysiology and treatment. However, much is still unknown, and a consensus is yet to be reached on how osteoporosis affects the jaw. With this in mind, the present study sought to identify changes over time in the mandibular cancellous bone of senile osteoporotic mice by assessing the trabecular structure in their mandible and tibia. The senescence-accelerated mouse strain P6 (SAMP6) (n = 5) was used as the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The findings of the present study on OVX 16-week-old SAMP6 and SAMR1 mice showed that BV/TV and Tb.N were significantly lower in the Group A mice sacrificed 1 week after OVX, but did not reveal any differences in the trabecular structure of the Group C and Group D mice sacrificed 4 weeks after OVX. Our data from the 17-and 20-week-old SAMP6 and SAMR1 mice under the same experimental conditions of Noguchi indicated that there was a characteristically rapid and significant decrease in trabecular bone after OVX 9) , but that this decrease tapered off in the SAMP6 mice 4 weeks after OVX to a similar level of standard OVX mice. Timewise comparison of the same mouse strains showed that the Group A mice had significantly higher BV/TV, Tb.Th, and Tb.N values than in Group C, and that Group B had significantly higher BV/TV and Tb.N values than in Group D. This finding suggests that OVX SAMP6 mice have finer trabecular thickness than that of standard SAMP6 mice.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The findings of the present study on OVX 16-week-old SAMP6 and SAMR1 mice showed that BV/TV and Tb.N were significantly lower in the Group A mice sacrificed 1 week after OVX, but did not reveal any differences in the trabecular structure of the Group C and Group D mice sacrificed 4 weeks after OVX. Our data from the 17-and 20-week-old SAMP6 and SAMR1 mice under the same experimental conditions of Noguchi indicated that there was a characteristically rapid and significant decrease in trabecular bone after OVX 9) , but that this decrease tapered off in the SAMP6 mice 4 weeks after OVX to a similar level of standard OVX mice. Timewise comparison of the same mouse strains showed that the Group A mice had significantly higher BV/TV, Tb.Th, and Tb.N values than in Group C, and that Group B had significantly higher BV/TV and Tb.N values than in Group D. This finding suggests that OVX SAMP6 mice have finer trabecular thickness than that of standard SAMP6 mice.…”
Section: Discussionmentioning
confidence: 81%
“…Studies by Noguchi et al and Chen et al have already shown that tibial trabecular structure is significantly thinner in SAMP6 mice than in their SAMR1 counterparts 9,18) . The findings of the present study on OVX 16-week-old SAMP6 and SAMR1 mice showed that BV/TV and Tb.N were significantly lower in the Group A mice sacrificed 1 week after OVX, but did not reveal any differences in the trabecular structure of the Group C and Group D mice sacrificed 4 weeks after OVX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The region of interest (ROI) was 1-mm-thick and positioned 0.5 mm above the growth plate. Bone mineral density, bone volume/tissue volume, trabecular number, trabecular thickness, trabecular separation, and marrow space star volume were semi-automatically determined in accordance with the guidelines for evaluation of bone microstructure using 3D images [24,25].…”
Section: Morphometric Evaluation Of Trabecular Bonementioning
confidence: 99%